How Much!? Determining the Cost of an Assignment in an Organic Chemistry Class. Issue 3 (3rd July 2019) - Kromer, John
ABSTRACT: Students in Organic Chemistry for Majors were required to write a paper as the culminating course assignment. Prior to completing this assignment, students could attend a library instruction session covering relevant databases and resources. Upon submission of their papers, bibliographies from 53 students were collected. Calculations were made to attempt a holistic account of costs associated with completing the assignment. Factors such as the cost of journals, databases, and librarian time were all included in the overall cost estimate, totalling 7, 189.22 for this single assignment.